Resveratrol-loaded cumin seed oil nanoemulsion ameliorates neurodegeneration in mice by inhibiting apoptosis, inflammation, and oxidative DNA damage - Shaymaa Eissa; Mohamed Elsayed; Azza Gawish; Heba ELzorkanay; Salwa Sabet (Nanomedicine Journal)
Objective(s): Neurodegenerative diseases affect over 50 million people worldwide. Unfortunately, there are no cures for these diseases, so finding effective treatments to improve human health is crucial. Resveratrol (Res) has neuroprotective effects due to its antioxidant and anti-inflammatory properties. However, Res is limited by poor water solubility and bioavailability. Therefore, the current study aimed to overcome Res’s limitations using recent nanotechnology.Materials and Methods: Resveratrol was loaded onto a nanoemulsion of cumin seed oil (CSONEs). The CSONEs and Res-CSONEs were characterized. Additionally, we investigated the neuroprotective effects of Res-loaded CSONEs in mice with Trimethyltin (TMT)-induced neurodegeneration. Thirty mice were divided into control, vehicle, TMT, TMT-CSONEs, TMT-Res, and TMT-Res-CSONEs. Each group received intraperitoneal treatment six times per week for two weeks. oxidative stress biomarkers, DNA damage extent, and histopathological evaluations were assessed in brain and liver tissues. In addition, the mRNA expression of apoptotic and inflammatory genes (Bax/Bcl2 and il-1β) and immunohistochemical staining of tau protein were evaluated in the brain tissues. Results: The Res-CSONEs improved cellular homeostasis by increasing GSH, and SOD, and decreasing MDA levels while decreasing the DNA damage parameters. They also decreased the expression of apoptotic and inflammatory genes and reduced the aggregation of tau protein. Histopathological examination of the studied tissues showed improvement in Res and Res-CSONEs compared to TMT. Conclusion: Loading Res on CSONEs resulted in promising neuroprotective effects due to its solubility and bioavailability enhancement. Combining the antioxidant and anti-inflammatory properties of both Res and CSONEs resulted in perfect neuroprotective effects on the brain tissues of mice.